Composition and Organization of Acute Ischemic Stroke Thrombus: A Wealth of Information for Future Thrombolytic Strategies - Desilles, Jean-Philippe; Di Meglio, Lucas; Delvoye, Francois; Maïer, Benjamin; Piotin, Michel; Ho-Tin-Noé, Benoît; Mazighi, Mikael (Frontiers in Neurology, 2022)
During the last decade, significant progress has been made in understanding thrombus composition and organization in the setting of acute ischemic stroke (AIS). In particular, thrombus organization is now described as highly heterogeneous but with 2 preserved characteristics: the presence of (1) two distinct main types of areas in the core—red blood cell (RBC)-rich and platelet-rich areas in variable proportions in each thrombus—and (2) an external shell surrounding the core composed exclusively of platelet-rich areas. In contrast to RBC-rich areas, platelet-rich areas are highly complex and are mainly responsible for the thrombolysis resistance of these thrombi for the following reasons: the presence of platelet-derived fibrinolysis inhibitors in large amounts, modifications of the fibrin network structure resistant to the tissue plasminogen activator (tPA)-induced fibrinolysis, and the presence of non-fibrin extracellular components, such as von Willebrand factor (vWF) multimers and neutrophil extracellular traps. From these studies, new therapeutic avenues are in development to increase the fibrinolytic efficacy of intravenous (IV) tPA-based therapy or to target non-fibrin thrombus components, such as platelet aggregates, vWF multimers, or the extracellular DNA network.